Treatment and prevention of intraocular pressure increase after ophthalmic surgeries - A. A. Antonov; I. V. Kozlova; D. V. Kosova (Российский офтальмологический журнал)
The literary review is focused on reactive hypertension after eye surgeries. Possible causes of increased intraocular pressure are described. Methods of therapy and prevention of reactive hypertension after cataract phacoemulsification and intravitreal injections are analyzed. Literary data show an emphasis on the efficacy and safety of applying a fixed combination of brimonidine and timolol.